Clinical outcomes and patient-reported measures in HCV care: Insight from a longitudinal prospective study in a large Italian region - Giaele Moretti; Maria Paola Tramonti Fantozzi; Ilaria Corazza; Erica De Vita; Milena Vainieri; Lara Tavoschi (PLoS ONE, 2026)
Background Hepatitis C virus (HCV) infection remains a critical public health issue worldwide. Direct-acting antivirals (DAAs) have revolutionized the treatment of hepatitis C. However, real-world elimination efforts are hindered by barriers in diagnosis, treatment access, and follow-up. Embedding patient-reported outcome measures (PROMs) and patient-reported experience measures (PREMs) into routine care may improve service delivery. This study evaluates clinical and patient-reported outcomes in the HCV care cascade in Tuscany (Italy), offering insights into how health service organization affects effectiveness, equity, and patient experience. Methods We conducted a multicenter, longitudinal, prospective study on 953 adults with HCV chronic infection. These adults were treated between 2021 and 2023 in seven prescribing centers in Tuscany. Clinical data included demographics, comorbidities, fibrosis staging, virological response (SVR12), and loss to follow-up (LTFU). PROMs and PREMs were collected at baseline (T0), 3 months post-treatment (T1), and 6 months after T1 (T2). We used the SF-12 tool and custom surveys. Patients were stratified by referral source (GPs, harm reduction services/prison, specialists). Clinical and questionnaire data were analyzed separately. Statistical analyses included ANOVA, Chi-square, Kruskal-Wallis, Cochran’s Q, Friedman, and repeated measures ANOVA with Bonferroni corrections. Significance was set at p ≤ 0.05. Results DAA therapy achieved high clinical efficacy: SVR12 was reached in 93.4% of patients. The rate rose to 98.6% when excluding those lost to follow-up. Patients referred by harm reduction/prison services were younger and mostly male. They had higher psychiatric comorbidities and risk behaviors. PROMs demonstrated significant improvements in perceived physical and emotional health following treatment, particularly among individuals referred by GPs and specialists. PREMs revealed increasing satisfaction with referring doctors over time. Satisfaction with specialist care remained high and stable. Referral pathways markedly influenced patient profiles and reported outcomes. There were notable disparities in experience and quality-of-life indicators. Conclusions This study highlights the importance of integrating clinical and patient-reported data in monitoring HCV care. High SVR rates confirm the effectiveness of DAAs, while PROMs and PREMs provide valuable insight into patient engagement and equity of access. Stratified analyses reveal the need for tailored approaches across care pathways, and high-risk populations require special attention. Embedding patient voice in evaluation fosters a more responsive, people-centered health system, advancing progress toward HCV elimination.